Children’s sleep and daytime functioning: Increasing heritability and environmental associations with sibling conflict - Breitenstein, Reagan S (Soc Dev, 2018)
Children’s sleep has both environmental and genetic influences, with stressful family environmental factors like household chaos and marital conflict associated with sleep duration and quality (El-Sheikh, Buckhalt, Mize, & Acebo, 2006; Fiese, Winter, Sliwinski, & Anbar, 2007). However, it is less clear whether sibling conflict is related to sleep duration and children’s sleep problems (e.g., nighttime wakings, parasomnias). In addition, few studies have tested whether associations between sleep and stressful family environmental factors are accounted for by an underlying set of genes or shared and unique environmental factors. Participants were 582 twins with sleep assessed longitudinally at 12, 30 months, and 5 years of age. Sibling conflict was assessed at 5 years. Greater sibling conflict was associated with shorter sleep duration and greater number of total sleep problems, over and above the influence of general household stress and other covariates. The heritability of sleep duration increased with age. Shared environmental factors accounted for the covariance between sibling conflict and sleep duration and total sleep problems. Findings hold promise for interventions, including educating parents about fostering positive sibling relationships and healthy sleep habits.